Coagulation and Skin Autoimmunity - Cugno, Massimo; Borghi, Alessandro; Garcovich, Simone; Marzano, Angelo Valerio (Frontiers in Immunology, 2019)
Several lines of evidence indicate that the immune system, inflammation and coagulation are simultaneously activated in autoimmune and immune-mediated skin diseases. Proinflammatory cytokines such as interleukin-6 and tumor necrosis factor-alpha induce the expression of the main initiator of coagulation, i.e. tissue factor. The proteases of coagulation in turn act on protease-activated receptors inducing the expression of various proinflammatory cytokines triggering inflammation. The cross-talk among immune system, inflammation and coagulation amplifies and maintains the activation of all three pathways. This review focuses on three skin disorders as chronic spontaneous urticaria (CSU), angioedema and bullous pemphigoid (BP), in which the relationships among the three systems have been investigated or their clinical consequences are relevant. Moreover, other immune-mediated inflammatory skin diseases are described like atopic dermatitis, psoriasis and dermatitis herpetiformis, in which the interplay among the three systems has been only preliminarily assessed. Markers of thrombin generation, fibrinolysis and inflammation have been reported to be increased in the plasma during flares of CSU and angioedema, as well as in the active phase of BP, with the marker levels reverting to normal during remission. The coagulation activation seems to be important only at local level in CSU and angioedema while both at local and systemic levels in BP which is the only condition associated with an increased thrombotic risk. On the basis of few available data, a prothrombotic state can be hypothesised also in psoriasis, atopic dermatitis and dermatitis herpetiformis. The prothrombotic state in autoimmune skin diseases raises the question of the indication of anticoagulant treatment, particularly in the presence of other cardiovascular risk factors.